TCQA, A Natural Caffeoylquinic Acid Derivative Attenuates H2O2-Induced Neuronal Apoptosis by Suppressing Phosphorylation of MAPKs Signaling Pathway - Yang, Yue; Ding, Yufang; Gao, Huan; Jiang, Xiaowen; Zhao, Qingchun (Planta Medica, 2021)
1,3,5-Tri-O-caffeoyl quinic acid is a caffeoylquinic acid derivative isolated from the roots of Arctium lappa L. Our previous studies have revealed that the ethyl acetate extract of the roots of A. lappa L. and the caffeoylquinic acids contained in it possess antioxidant properties, especially 1,3,5-tri-O-caffeoyl quinic acid. The present study aimed to investigate the protective effects of 1,3,5-tri-O-caffeoyl quinic acid against hydrogen peroxide-induced oxidative stress and explore the underlying mechanism. We found that 1,3,5-tri-O-caffeoyl quinic acid prevented the decline of cell viability and excessive release of lactate dehydrogenase induced by hydrogen peroxide. In addition, Hoechst 33 342 staining and Annexin V-PI double staining showed that 1,3,5-tri-O-caffeoyl quinic acid inhibited hydrogen peroxide-induced neuronal cell apoptosis. 1,3,5-Tri-O-caffeoyl quinic acid reduced the excessive production of intracellular reactive oxygen species, decreased the malondialdehyde content, and improved the activity of superoxide dismutase. Furthermore, 1,3,5-tri-O-caffeoyl quinic acid restored the loss of mitochondrial membrane potential in SH-SY5Y cells induced by hydrogen peroxide. 1,3,5-Tri-O-caffeoyl quinic acid downregulated the overexpression of proapoptotic proteins, including Bax, cytochrome c, cleaved caspase-9, and cleaved caspase-3 as well as promoted the expression of the antiapoptotic protein Bcl-2. Moreover, the phosphorylation of mitogen-activated protein kinases induced by hydrogen peroxide was inhibited by 1,3,5-tri-O-caffeoyl quinic acid. Pretreatment with 1,3,5-tri-O-caffeoyl quinic acid also promoted the activation of phosphorylated Akt. Taken together, these findings suggest that 1,3,5-tri-O-caffeoyl quinic acid exerts protective effects against hydrogen peroxide-induced neuronal apoptosis. In addition, inhibition of the mitogen-activated protein kinase signaling pathway and the activation of Akt are implicated in the antioxidant activity of 1,3,5-tri-O-caffeoyl quinic acid, giving new insight in searching for a compound with antioxidant activity for the treatment of oxidative stress-associated neurological diseases.
Keywords: Arctium lappa L.; composite; TCQA; H2O2− apoptosis; oxidative stress